Gellan Gum-based Bioink for Bioprinting of a Mechanically Mimetic 3D in vitro Liver Model - Kohori, Natália Akemi [UNESP]; Cengiz, Ibrahim Fatih; Carvalho, Mariana; Silva-Correia, Joana; Pires, Ricardo A.; Riccardi, Carla dos Santos [UNESP]; Pereira, Lilian Cristina [UNESP]; Reis, Rui L.; Oliveira, Joaquim Miguel (Springer Nature, 2025)
The liver is vital for the human body's metabolism, making the development of more predictable and reproducible pathophysiological-relevant three-dimensional (3D) liver models crucial for studying the accumulation of xenobiotics and associated liver diseases. In this work, we describe the development of a bioink comprising 0.2% w/v TayaGel® HA (high acyl gellan gum) and 1.2% w/v Gelzan™ CM (low acyl gellan gum) for the bioprinting of 3D liver models. The bioink underwent physicochemical characterization, including rheological and dynamic mechanical analyses, and cytotoxicity testing using HepG2 cell line in vitro. The shape fidelity assay suggested an ink fluid-like behavior and good filament formation with Young's modulus resembling liver tissue. Moreover, the dynamic mechanical analysis showed the tan δ aligned with liver tissue, while the hydrogel degraded over 60% within 24 h. No increase in cell number and low viability were observed in loaded cells during 7 days of cultivation. Furthermore, the hydrogel presented a non-angiogenic nature on the chicken chorioallantoic membrane model. Collectively, these findings highlight the potential of gellan gum (GG), particularly high acyl gellan gum, as a bioink due to its mechanical mimicry and suitability for bioprinted 3D in vitro as sacrificial bioink, combining soft-elastic properties with controlled degradation.